Perencanaan Lanskap Monumen Pahlawan Perang Kemerdekaan Republik Indonesia 1945, Taman Mumbul, Nusa Dua, Bali. - SONY ALI ANSHORI; LURY SEVITA YUSIANA; NI WAYAN FEBRIANA UTAMI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2012)
ABSTRACT Landscape Planning of Republic of Indonesia Independence War Monument in Taman Mumbul Nusa Dua, Bali. Monument to Heroes of the War of Independence of the Republic of Indonesia in 1945, Taman Mumbul, Nusa Dua, Bali was built to commemorate and appreciate local Balinese who fought for freedom from colonialism in the past. This study aims to plan memorial landscape in Taman Mumbul Nusa Dua, Bali in harmony with the meaning of 1945 independence war monument of Republic of Indonesia and also has function as an urban park. The concept of the planning is to reinforces the meaning of the monument which is represented the struggle of the heroes to achieve independence in a green open space and to develope the site as an urban park for local people. This landscape planning harmonized the monument with the `heroism` philosophy and combined with the theme of `tapak tilas` on the main zone. The vegetation uses as an elements to appreciate the struggle of heroes in a green open space. The planning is also to create a place for recreation and socialize for local people or monument visitors. Keywords: landscape planning, historical monument, heroism, urban park.